Brain mapping: a novel intraoperative neuropsychological approach - Skrap, Miran; Marin, Dario; Ius, Tamara; Fabbro, Franco; Tomasino, Barbara (Journal of neurosurgery, 2016)
OBJECTIVE Awake surgery and mapping are performed in patients with low-grade tumors infiltrating functional brain areas for which the greater the resection, the longer the patient survival. However, the extent of resection is subject to preservation of cognitive functions, and in the absence of proper feedback during mapping, the surgeon may be less prone to perform an extensive resection. The object of this study was to perform real-time continuous assessment of cognitive function during the resection of tumor tissue that could infiltrate eloquent tissue. METHODS The authors evaluated the use of new, complex real-time neuropsychological testing (RTNT) in a series of 92 patients. They reported normal scoring and decrements in patient performance as well as reversible intraoperative neuropsychological dysfunctions in tasks (for example, naming) associated with different cognitive abilities. RESULTS RTNT allowed one to obtain a more defined neuropsychological picture of the impact of surgery. The influence of this monitoring on surgical strategy was expressed as the mean extent of resection: 95% (range 73%-100%). At 1 week postsurgery, the neuropsychological scores were very similar to those detected with RTNT, revealing the validity of the RTNT technique as a predictive tool. At the follow-up, the majority of neuropsychological scores were still > 70%, indicating a decrease of < 30%. CONCLUSIONS RTNT enables continuous enriched intraoperative feedback, allowing the surgeon to increase the extent of resection. In sharp contrast to classic mapping techniques, RTNT allows testing of several cognitive functions for one brain area under surgery.